2010
DOI: 10.1021/ie901616n
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical Phase Inversion To Form Drug-Loaded Poly(vinylidene fluoride-co-hexafluoropropylene) Membranes

Abstract: Membranes loaded with an active principle are one of the alternatives proposed to obtain controlled release pharmaceutical formulations. Until now, several methods have been proposed for the fabrication of membranes as drug delivery devices, such as phase inversion, gas foaming/particulate leaching, and solvent evaporation. Supercritical CO2 (SC-CO2) phase inversion offers an alternative process to obtain solvent-free membranes with short processing times, avoiding the collapse of the structure. We prepared po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Because of the absence of a liquid-vapor interface, porous membranes can be prepared without collapse of structure; supercritical CO 2 not only induce phase separation but also dry the formed membrane meanwhile; the organic solvent dissolved in supercritical CO 2 allows to be extremely removed by simply diminishing the pressure. 12 Generally speaking, polymer crystallinity and the resultant membrane morphology are among important factors in determining the physical and chemical properties of membrane. It is widely accepted that, PVDF chains can crystallize into at least four distinct phases or forms, which are a (form II), b (form I), c (form III), and d (form IV).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the absence of a liquid-vapor interface, porous membranes can be prepared without collapse of structure; supercritical CO 2 not only induce phase separation but also dry the formed membrane meanwhile; the organic solvent dissolved in supercritical CO 2 allows to be extremely removed by simply diminishing the pressure. 12 Generally speaking, polymer crystallinity and the resultant membrane morphology are among important factors in determining the physical and chemical properties of membrane. It is widely accepted that, PVDF chains can crystallize into at least four distinct phases or forms, which are a (form II), b (form I), c (form III), and d (form IV).…”
Section: Introductionmentioning
confidence: 99%
“…A c c e p t e d M a n u s c r i p t However, there are several works in the literature on membrane production using SC-induced phase separation, for various applications [132][133][134][135][136][137] and also for biomedical field [138,139]; but, nanostructure in some cases is not present. Tsivintzelis et al [140] prepared porous scaffolds of PLLA, a biocompatible and biodegradable polymer, and investigated the effect of pressure, temperature and initial concentration of the polymer solution on the final structure; but, nanostructure was absent.…”
Section: Supercritical Assisted Phase Separationmentioning
confidence: 99%
“…SC-assisted phase separation was also applied for the production of drug carriers; i.e., nanoporous membranes loaded with an active principle. Cardea et al [147] used this process to produce Polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) membranes loaded with the antibiotic Amoxicillin. The authors observed that when SC-CO 2 solvent power was high, the phase separation was rapid and solid-liquid demixing was obtained, leading to a nanometric structure with a mean pore diameter of about 150 nm.…”
Section: Supercritical Assisted Phase Separationmentioning
confidence: 99%
“…From the use of carbon dioxide as a drying agent in supercritical fluid drying, to the use of carbon dioxide as a plasticizing agent in gas foaming and sintering or the use of carbon dioxide as an anti-solvent in the supercritical assisted phase inversion method, almost all encounter a way to satisfy most of the characteristics requested. A summary of the features of the different technologies and some examples of drug delivery systems for tissue engineering and regenerative medicine applications are listed in Table 12.3 [78][79][80][81][82][83][84][85][86][87][88]. Hydrogel foaming is a more recent technique which has been explored for the preparation of porous scaffolds and in this process hydrogels foaming involves the dissolution of carbon dioxide in the water phase present on the hydrogel which will promote foaming of the structure upon depressurization [89,90].…”
Section: Drug Delivery In Tissue Engineering Applicationsmentioning
confidence: 99%
“…Starch-poly-lactic acid blend impregnated with dexamethasone [84] Poly(vinylidene fluoride-cohexafluoropropylene) loaded with amoxicillin [85] Poly-methylmethacrylate loaded with amoxicilin [86]…”
Section: Technique Principle Examples Of Drug Delivery Systems Preparmentioning
confidence: 99%